Landscape of Prognostic m6A RNA Methylation Regulators in Hepatocellular Carcinoma to Aid Immunotherapy - Xu, Qianhui; Xu, Hao; Deng, Rongshan; Li, Nanjun; Mu, Ruiqi; Qi, Zhixuan; Shen, Yunuo; Wang, Zijie; Wen, Jingchao; Zhao, Jiaxin; Weng, Di; Huang, Wen (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background: Hepatocellular carcinoma (HCC) ranks the sixth prevalent tumors with high mortality globally. N6-methyladenosine (m6A) might act an important factor in tumorigenesis. Methods: To reveal the landscape of tumor immune microenvironment (TIME) in HCC, ESTIMATE algorithm, ssGSEA method and CIBERSORT analysis were conducted. Taking advantage of consensus clustering, two different HCC categories were screened. We analyzed the correlation of clustering results with TIME and immunotherapy. Then we yielded a risk signature by systematical bioinformatics analyses. Immunophenoscore (IPS) was implemented to estimate immunotherapeutic significance of risk signature. Results: The m6A-based clusters were significantly correlated with overall survival (OS), immune score, immunological signature, immune infiltrating, and ICB-associated genes. Risk signature possessed robust prognostic validity and significantly correlated with TIME context. Immunophenoscore was employed as a surrogate of immunotherapeutic outcome, patients with low-risk scores presented significantly higher immunophenoscore. Conclusions: Collectively, m6A-based clustering subtypes and signature was a robust prognostic indicator and correlated with TIME and immunotherapy, contributing to clinical management and prognosis prediction of HCC.